2020
DOI: 10.1680/jstbu.19.00011
|View full text |Cite
|
Sign up to set email alerts
|

Finite-element modelling of concrete-filled steel tube columns wrapped with CFRP

Abstract: Experimental evaluation of the structural behavior of concrete-filled tubular (CFT) circular steel columns under the combined effects of axial and cyclic lateral loads is costly and challenging. Therefore, this study provides a nonlinear finite element analysis (FEA) of 21 models for CFT circular steel columns wrapped with a number of carbon fiber reinforced polymer (CFRP) composites layers at its end region, which represents the critical location in terms of the lateral load capacity. The intent is to confine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It is worth mentioning that the SOLID65 element is distinguished for having the capabilities of cracking, crushing, and plastic deformation in three perpendicu-lar directions. However, in this experimental work, the SOLID65 element's capability of crushing failure has been overlooked because this type of failure was not noticed when the load was applied [23][24][25][26][27][28][29][30]. Hence, the simulated models' tensile strains depended only on ultimate failure and emerging of cracking [23][24][25][26][27][28][29][30].…”
Section: Modeling Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that the SOLID65 element is distinguished for having the capabilities of cracking, crushing, and plastic deformation in three perpendicu-lar directions. However, in this experimental work, the SOLID65 element's capability of crushing failure has been overlooked because this type of failure was not noticed when the load was applied [23][24][25][26][27][28][29][30]. Hence, the simulated models' tensile strains depended only on ultimate failure and emerging of cracking [23][24][25][26][27][28][29][30].…”
Section: Modeling Methodologymentioning
confidence: 99%
“…However, in this experimental work, the SOLID65 element's capability of crushing failure has been overlooked because this type of failure was not noticed when the load was applied [23][24][25][26][27][28][29][30]. Hence, the simulated models' tensile strains depended only on ultimate failure and emerging of cracking [23][24][25][26][27][28][29][30]. The used Poisson's ratio for concrete ranges from 0.15 to 0.22 thus a representative value of 0.2 was selected [34].…”
Section: Modeling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…2 (AN-SYS 2009). With the assumption of the cleanness of the steel and sufficient adhesion of the core concrete to the steel (perfect bond with no slip assumption), the coincident nodes of the steel and the core concrete can be connected to each other by merging (Abdalla et al 2020). In this research, no contact element was used and assumed a perfect bond by merging the coincide nodes of steel and core concrete.…”
Section: Finite Element Modeling Of Concretefilled Steel Columnsmentioning
confidence: 99%
“…Ozbakkaloglu et al (2013) developed the axial stress-strain behavior of FRP-confined concrete in circular sections, and the database containing the test results of 730 FRP-confined concrete cylinders under monotonic axial compression. Abdalla et al (2019) carried out a non-linear finite element analysis on circular concrete-filled steel tubes whose end regions were confined by CFRP, and research results showed that the use of CFRP composites resulted in an increase in the lateral load, drift capacities and energy dissipation. In review of the previous studies, it is found that the axial compress behavior of FRP confined concrete is the most important topic of the concrete-filled FRP tubular columns (Issa et al, 2009;Al-Rousan and Issa, 2018).…”
Section: Introductionmentioning
confidence: 99%